ANALISIS PENGARUH ROA, NPM, DER, DAN SIZE TERHADAP PRAKTIK PERATAAN LABA (Studi kasus pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2007-2010) - Shintia Dewi, Kartika; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2012)
Income smoothing is defined as an intentional act done to reduce the fluktuation of profit managers to use certain accounting methods. The reason that income smoothing performed by the managemen tare: reduce tax debt, increase investor confidence, can strengthen the relationship between managers and employees The study was conducted using purposive sampling for sampling is used and there are 53 companies that were visited during the study. Analytical techniques used in this study is multiple regression analysis using SPSS where previous data was tested using the classical assumption test. The results show net profit margin (NPM) and size significantly positively related to income smoothing while the return on assets (ROA) and debt to equity ratio (DER) are not significant to earnings smoothing.